Characteristics of Soils of Lower Indo-Gangetic Plains of West Bengal under Rice Cultivation - S.K. Gangopadhyay (Journal of the Indian Society of Soil Science, 2022)
Five typical pedons developed from alluvium on lower Indo-Gangetic plain under major land use system of rice from Murshidabad district, West Bengal were studied for their morphological, physical and chemical characteristics. Soils were very deep with varying texture and drainage classes and have some common characters during pedogenesis under impeded drainage condition. Soils were characterized by the redoximorphic features viz., mottle in the form of segregation of Fe-Mn depletion or gleying, mostly in the sub-surface to sub-soil. Soils were strongly acidic (pH 5.1) to slightly alkaline in the surface and neutral (pH 6.5 to 7.5) in the sub-surface to sub-soil, low to high in soil organic carbon (SOC) content (0.40 to 9.60 g kg-1), low to medium in cation exchange capacity (CEC) [4.0 to 42.0 cmol(p+)kg-1] with high base saturation (61 to 90%). Among the exchangeable bases, Ca2+ is the dominant cation followed by Mg2+, Na+ and K+ . Low to medium CEC of soil indicates the mineralogy of the soil as kaolinite and illite (mica). However, clay CEC value indicates the presence of smectite along with hydroxyl-interlayered vermiculite. The high clay CEC value with neutral soil reaction and high content of Ca2+ indicates the dominance of smectite in the soils of pedons 2 and 3. The SOC stock suggested implementation of appropriate conservation measures to the soils of young alluvial plains to improve the quality of soil. The soils of old alluvial plains are generally more fertile in comparison to that of the young alluvial plains. The study indicates that land use has got significant effect on soil characteristics, influencing the soil fertility.